2001
DOI: 10.1093/carcin/22.6.917
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitution variants of APE1 and XRCC1 genes associated with ionizing radiation sensitivity

Abstract: Although several variants of DNA repair genes have been identified, their functional significance has not been determined. Using samples collected from 135 cancer-free women, this study evaluated whether amino acid substitution variants of DNA repair genes contribute to ionizing radiation (IR) susceptibility as measured by prolonged cell cycle G2 delay. PCR-restriction fragment length polymorphism (RFLP) assays were used to determine four genotypes: X-ray repair cross complementing group 1 (XRCC1, exon 6, C/T,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
180
6
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(198 citation statements)
references
References 36 publications
10
180
6
2
Order By: Relevance
“…These results are in accord with our findings that the wild-type genotypes of both XPD and XRCC1 are associated with shorter cancer-specific survival in muscle-invasive bladder cancer patients treated with CRT. However, the results of Hu et al (2001) seem to contradict those of Sak et al (2005) noted above. Sak et al (2005) stated that one possible explanation is that the reduced expression of XRCC1 and APE1 merely reflects the poorly differentiated nature of tumour cells in more aggressive tumours, and that cells from aggressive tumours with extensive genomic instability could contain chromosomal aberrations that result in the failure of transcription of genes, including DNA repair genes, thus resulting in lower protein expression of the gene products.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…These results are in accord with our findings that the wild-type genotypes of both XPD and XRCC1 are associated with shorter cancer-specific survival in muscle-invasive bladder cancer patients treated with CRT. However, the results of Hu et al (2001) seem to contradict those of Sak et al (2005) noted above. Sak et al (2005) stated that one possible explanation is that the reduced expression of XRCC1 and APE1 merely reflects the poorly differentiated nature of tumour cells in more aggressive tumours, and that cells from aggressive tumours with extensive genomic instability could contain chromosomal aberrations that result in the failure of transcription of genes, including DNA repair genes, thus resulting in lower protein expression of the gene products.…”
Section: Discussionmentioning
confidence: 55%
“…Ionising radiation exposure damages cellular DNA in many ways, requiring the concerted action of a number of DNA repair enzymes to restore genomic integrity (Hu et al, 2001). The BER and HRR pathways are particularly important with regard to this (Thompson and West, 2000;Khanna and Jackson, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 399Arg>Gln is situated within the BRCT-1 region harboring the poly(ADP-ribose)polymerase-binding domain (Shen et al, 1998). A few previous studies reported that the 399Gln allele was associated with a higher level of DNA adducts and glycophorin A mutations (Lunn et al, 1999;Matullo et al, 2001a, b), increased sister chromatin exchange frequencies (Duell et al, 2000), or higher sensitivity to ionizing radiation and chemical mutagens (Hu et al, 2001;Wang et al, 2003a, b). However, conflicting results also exist, showing no association between the 399Arg>Gln polymorphism and DNA adduct levels (Matullo et al, 2001a, b;Palli et al, 2001).…”
Section: Discussionmentioning
confidence: 99%